Polymer-enhanced perovskite oxide-based photocatalysts: a review - Thien G.S.H.; Chan K.-Y.; Marlinda A.R.; Yap B.K. (Royal Society of Chemistry, 2024)
Oxide perovskites (OPs) have emerged as promising photocatalysts for numerous applications, such as energy conversion, renewable fuels, and environmental remediation. Although OPs are gaining traction, their efficacies are still hindered by low charge carrier mobility and poor stability. This study investigated the function of polymers actively participating in OP structures to improve the overall characteristics. An overview of the polymer-enhanced perovskite oxide photocatalyst (PEPOP) field was effectively reviewed. These PEPOPs were demonstrated in photovoltaics, pollutant degradation, and gas conversion and reduction. Nonetheless, additional research is needed to explore the potential of PEPOPs to establish their efficacy in photocatalytic applications. The technological improvements of PEPOPs were hindered by significant challenges related to stability and sensitivity. The urgency of this review was apparent due to the fast-paced nature of research in the field of photocatalysis. Recent breakthroughs and emerging applications highlight the need for a comprehensive overview of PEPOPs and their enhanced catalytic capabilities. Consequently, a broad outlook was provided for the current state of PEPOP-related studies, highlighting the potential of these materials for future applications. 2023 The Royal Society of Chemistry.